(3JWHjbGJ HMhK GdYedjGJ aj GdGOGQIs - (3UGdM egOj eMSf(B, (3GdYGeQjs; (3YhGWa GHQGgje GdMOGO(B, s ((3YeGf(B:s (3GKQGA ddfTQ(B,s, 2009)
(3HMhK GdYedjGJ (B: (3eaGgje CSGSjI , fXQjI GdbQGQGJ (B: (3UfY h EJNGP GdbQGQ, GdHQeLI GdNWjI UjGZI eSGFd GdHQeLI GdNWjI aj Md GdeTcdGJ GdCOGFjI GdWQjbI GdHjGfjI , GdHQeI GdNWjI (B: (3GdWQjbIGdeHSWI , GdWQjbI GdKfGFjI , eTcdI Gdfbd , feGPL Gdfbd eJYOO GdeQGMd , GdJNUjU , fXQjI Uaha GdGfJXGQ, EOGQI h JNWjW GdeTGQjY , feGPL QbGHI GdeNRhf h feGPL GdeMGcGI (B.s
Keywords: (3EOGQI GdGYeGds; (3GdGOGQIs; (3HMhK GdYedjGJs